Assessment of Primary Schools Teachers’ Knowledge and Attitudes toward Communicable Diseases Prevention and Control at Primary Schools - Mohammed Abbas Hussein1, Muna Abdul Wahab Khalil2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Communicable diseases are illnesses that transmitted from a person, animal, or inanimate source to another person either directly or indirectly. Illnesses caused by communicable diseases are common among school students because of overcrowding. Objectives: The purpose of the study is to assess the knowledge and attitudes of primary school teachers toward communicable diseases prevention and control and to find out the relationship between the primary school teachers’ knowledge and attitudes with their personal and socio-demographic characteristics. Methodology: A descriptive cross-sectional study design using a simple random sample of (N=400) teachers working in primary schools through the period from October 2018 to June 2019. A questionnaire was created for this purpose. Its composed of (4) parts. The overall items included in the questionnaire are (55) items. A pilot study conducted to determine the reliability of the questionnaire, while the validity is obtained by distribution of the questionnaire through a panel of (15) experts. Statistical package for social sciences (SPSS) version (25) used for the analysis of the data. Appropriate statistical tests were used accordingly. Statistical analysis used: The data are coded and tested by the application (SPSS) through the descriptive and inferential analysis. Results: The study findings indicate that most of teachers (65.8%) had good knowledge toward communicable diseases prevention and control, also the highest percentage of teachers had agreed attitudes toward communicable diseases. Conclusions and recommendations: All teachers working with children may be at risk for getting communicable diseases, especially those with less years of experiences. Therefore, it is necessary to increase their awareness toward communicable diseases prevention and control through collaboration with ministry of health and environment and through education programs about communicable diseases and ways of prevention.